Forest resource in Peninsular Malaysia: a question of sustainability - Othman, Mohd Shahwahid; Zainalaludin, Zumilah (Universiti Putra Malaysia, 1994)
Peninsular Malaysia has achieved rapid economic growth in the forestry sector. During the period 1972 to 1992, log production increased one and one halftimes and earnings from the exporting of logs and wood products multiplied six and one half times. The above information explains the foward linkages supported by the forest resources. Since logging as an extractive activity, it is not clear to what extent the economic growth within the forestry sector has depleted the forest resource. The status of the above issues will be deliberated in a natural resource accounting framework.